Policies and Strategies for Improving the Research and Scientific Publications Quality at State Islamic Religious Colleges in Kalimantan - Muhammad Zainal Abidin; Muhamad Sabirin; Yulia Hafizah; Muhammad Yuseran (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2023)
The quality of research and scientific publications is an essential concern in managing higher education institutions. Therefore, this research aims to examine the policies and strategies for enhancing the quality of research and scientific publications in State Islamic Religious Colleges. This is a qualitative study that gathers data from library and field research. The findings show that each university already has regulations based on provisions from the Ministry of Higher Education, including the Internal Quality Assurance System (SPMI) and External Quality Assurance System (SPME), for managing research quality. Additionally, UIN Antasari Banjarmasin, UIN Samarinda, and IAIN Palangkaraya are improving the quality of research and scientific publications of their lecturers with policies such as allocating 30% of BOPTN funds and implementing the LITAPDIMAS system. However, the outputs and benefits of these policies have not been fully realized due to budget absorption issues that limit the development of a research and publication culture. Therefore, developing such a culture presents a significant challenge that requires a long-term commitment and the participation of all stakeholders. The culture-building process should start from upstream to downstream aspects.